FRI0034 GLUCOCORTICOID TREATMENT IS ASSOCIATED WITH LOWER EXTREMITY MUSCLE WASTING IN RHEUMATOID ARTHRITIS PATIENTS. (2nd June 2020) - Yang, L. J.; Ouyang, Z. M.; Yang, K. M.; Xu, Y. H.; Li, H. G.; Chen, C.; Lin, J. Z.; Dai, L.
Abstract : Background: Short-term (up to 3-4 months) glucocorticoids combined with methotrexate is recommended for initial therapy of active rheumatoid arthritis (RA) patients by EULAR, considering the long-term safety of glucocorticoids such as higher cardiovascular risk. However, in real-world clinical practice, glucocorticoids are widely used even up to 70% in refractory RA patients. Glucocorticoids can pharmacologically lead to enhancement of lipogenesis and muscle degradation. On the other hand, their anti-inflammatory effect can indirectly mitigate fat deposition and muscle catabolism. The overall effect of glucocorticoid therapy on body composition (BC) in RA patients remain elusive until now. Objectives: To investigate the characteristics of disease indicators, body mass index (BMI) and BC in RA patients with previous glucocorticoid treatment in a cross-sectional study. Methods: Consecutive RA patients were recruited and clinical data including disease activity, function and radiographic assessment were collected. BC including fat and muscle mass and their distributions was assessed by bioelectric impedance analysis. Multivariate multinomial logistic regression analysis was performed to identify the association of disease characteristics, BMI and BC with previous glucocorticoids treatment in RA patients, following the step-forward selection rule that variables were included in the equation when the P value was <0.05 or removed when the P value was >0.10. Results: (1) There were 620 RA patients recruited, the mean age was 49.5±12.8 years old, and the median disease duration was 48 months (IQR 23-108 months) with 82.3% female. There were 107 (17.3%) patients with treatment naïve (without previous glucocorticoids or DMARDs therapy for six months before enrollment), 333 (53.7%) with previous glucocorticoid therapy with or without previous DMARDs therapy, and 180 (29.0%) with previous DMARDs therapy only. (2) For disease characteristics aspect, there were significant differences in all core disease activity indicators, functional indicator, and radiographic assessment indicators among three subgroups. Compared with those with treatment naïve, RA patients with previous glucocorticoid therapy had lower disease activity indicators including 28TJC, 28SJC, PtGA, PrGA, PainVAS, ESR, CRP, DAS28-CRP, SDAI and CDAI, and lower HAQ-DI and lower rate of functional limitation (all P <0.0167). While compared with those with previous DMARDs therapy only, RA patients with previous glucocorticoid therapy had higher disease activity indicators including 28TJC, 28SJC, PtGA, PrGA, PainVAS, DAS28-CRP, SDAI and CDAI (all P <0.0167). (3) For BMI and BC aspects, there were significant differences in lower fat-free mass and lower muscle indicators among three subgroups. Compared with those with previous DMARDs therapy only, RA patients with previous glucocorticoid therapy showed lower fat-free mass and lower muscle indicators including appendicular muscle mass especially in both lower extremities (all P <0.0167). There was no difference in BMI and fat indicators among three groups. (4) Multivariate multinomial logistic regression analysis showed that compared with previous DMARDs therapy only, previous glucocorticoid therapy was positively associated with DAS28-CRP ( OR =1.289, 95% CI : 1.119-1.484, P <0.001), and negatively associated with lower extremity muscle mass ( OR =0.907, 95% CI : 0.840-0.979, P =0.013). Conclusion: Previous glucocorticoid treatment is associated with lower extremity muscle wasting. Further prospective study is needed to confirm their relationship. References: None. Acknowledgments Funding: This work was supported by National Natural Science Foundation of China (grant no. 81971527 and 81801606), Guangdong Natural Science Foundation (grant no. 2019A1515011928 and 2018A030313541), and Science and Technology Program of Guangzhou (grant No. 201904010088). Disclosure of Interests: None declared